Nurses’ Experiences of Providing Spiritual Care for Schizophrenic Patients in Psychiatric Hospital, Magelang: A Qualitative Study - Wijayanti, Diyan Yuli; Sari, Sri Padma; Sarjana, Widodo (Universitas Aisyah Pringsewu, 2024)
Spiritual interventions have received growing attention in recent years as they are evident to reduce psychotic symptoms significantly in patients with mental disorders. However, some nurses neglect patients' spiritual needs as it is not their primary responsibility. In other research, mental health nurses felt uncertain about spiritual issues and anxious to distinguish between spiritual needs and mental illness symptoms. Their concern about spiritual care being inappropriate within their practice setting and lack of knowledge also influence the willingness of nurses to provide spiritual care. This study aimed to explore nurses' experiences of providing spiritual interventions for patients with schizophrenia in Prof. Dr. Soerodjo's psychiatric hospital in Magelang, Indonesia. A descriptive qualitative study with a phenomenological approach was conducted among seven participants who were purposively recruited from different hospital wards. The researchers conducted semi-structured focused-group discussions (FGDs) and employed theoretical triangulation to improve the quality of data analysis. A thematic analysis was used to obtain rich, detailed, complex data reports. The results showed two major themes: (1) nurses' experiences providing spiritual interventions and (2) the importance of spiritual interventions for patients with schizophrenia. Spiritual interventions were crucial to patient care and were implemented in all hospital wards. These interventions varied in form, and their implementation merely relied on nurses' and patients' commitment and motivation. Some barriers to implementing spiritual interventions were reported, including stigma, lack of commitment, and suboptimal fulfillment of spiritual needs for patients other than Moslem. Implementation of spiritual interventions is best based on the prepared modules, which contain spiritual assessment tools, material, and guidelines for fulfilling the spiritual needs and the standard of spiritual intervention that will be provided. Nurses require strong commitment and motivation to carry out spiritual intervention to have a satisfying impact in the form of a decrease in violent behavior, confinement, length of stay, runaway rate, increased communication skills, self-control, and improved appearance. Schizophrenic patients are expected to continue their spiritual activities until they are ready to return to the community. Innovations and institutional support are required to help achieve the goals of spiritual interventions.